Peran Guru Dalam Membentuk Karakter Disiplin Siswa Kelas V SDN 42 Ampenan - Muhaimin Muhaimin; A. Hari Witono; Ilham Syahrul Jiwandono (Universitas Negeri Makassar, 2021)
This study aims to determine how the teacher's role in shaping the disciplinary character of the fifth-grade students of SDN 42 Ampenan. This research is motivated by the importance of shaping the character of discipline because currently there are many deviations that are far from noble character. This research uses descriptive qualitative research methods. Research location at SDN 42 Ampenan. Primary data sources are teachers and school principals, secondary data sources are the results of documentation. Data collection techniques using interviews and documentation. The data collected is in the form of words and pictures. Data analysis used the Miles, Humberman, and Saldana models, namely data collection, data condensation, data presentation, and data verification. The results showed that the form of the disciplinary character of students at SDN 42 Ampenan was time discipline, discipline in enforcing rules, discipline in attitude and discipline in worship, while the role of class V teachers in shaping the character of student discipline at SDN 42 Ampenan was the teacher as an educator, teacher, mentor, trainers, and evaluators. The results of this study are indicated by changes in attitudes and behavior of students in a better direction by reflecting the habit of obeying the rules in school.